Contrasting transcriptomic patterns reveal a genomic basis for drought resilience in the relict fir Abies pinsapo Boiss. (10th October 2022) - Cobo-Simón, Irene; Maloof, Julin N; Li, Ruijuan; Amini, Hajar; Méndez-Cea, Belén; García-García, Isabel; Gómez-Garrido, Jèssica; Esteve-Codina, Anna; Dabad, Marc; Alioto, Tyler; Wegrzyn, Jill L; Seco, José Ignacio; et al.
Abstract: Climate change challenges the adaptive capacity of several forest tree species in the face of increasing drought and rising temperatures. Therefore, understanding the mechanistic connections between genetic diversity and drought resilience is highly valuable for conserving drought-sensitive forests. Nonetheless, the post-drought recovery in trees from a transcriptomic perspective has not yet been studied by comparing contrasting phenotypes. Here, experimental drought treatments, gas-exchange dynamics and transcriptomic analysis (RNA-seq) were performed in the relict and drought-sensitive fir Abies pinsapo Boiss. to identify gene expression differences over immediate (24 h) and extended drought (20 days). Post-drought responses were investigated to define resilient and sensitive phenotypes. Single nucleotide polymorphisms (SNPs) were also studied to characterize the genomic basis of A. pinsapo drought resilience. Weighted gene co-expression network analysis showed an activation of stomatal closing and an inhibition of plant growth-related genes during the immediate drought, consistent with an isohydric dynamic. During the extended drought, transcription factors, as well as cellular damage and homeostasis protection-related genes prevailed. Resilient individuals activate photosynthesis-related genes and inhibit aerial growth-related genes, suggesting a shifting shoot/root biomass allocation to improve water uptake and whole-plant carbon balance. About, 152 fixed SNPs were found between resilient and sensitive seedlings, which were mostly located in RNA-activity-related genes, including epigenetic regulation. Contrasting gene expression and SNPs were found between different post-drought resilience phenotypes for the first time in a forest tree, suggesting a transcriptomic and genomic basis for drought resilience. The obtained drought-related transcriptomic profile and drought-resilience candidate genes may guide conservation programs for this threatened tree species.